Sacroiliac joint pain in adolescents: Diagnostic and treatment challenges. Issue 2 (11th May 2022) - Cucchiaro, Giovanni; Francis, Christopher; Householder, Kymberly; Fernandez, Allison
Abstract: The aim of this review was to assess diagnostic and treatment challenges of adolescents with SI joint pain. We diagnosed 13 of the patients who were referred to our chronic pain clinic because of low back pain (30%) with SI joint pain based on provocative tests response. We performed SI joint steroid infiltration. Six patients (46%) felt better immediately after the procedure and 1 (8%) patient had a one‐side only pain relief after a bilateral block. Four of these patients (31%) did not experience any further episode of pain during the follow‐up and three patients reported recurring pain on average 2 months after the initial procedure. The 2nd procedure was successful in two patients and the third one experienced pain again 12 months later, requiring a third successful infiltration. Six patients (46%) experienced pain again within a few hours or days after the infiltration and their pain score were unchanged compared with what they had reported prior to the procedure. We were unable to place the needle within the joint under fluoroscopy in 1 patient; however, we were successful repeating the procedure under CT guidance. One patient experienced a motor and sensory block in the distribution of the sciatic nerve immediately after the procedure, which resolved within 24 and 48 hours, respectively. SI joint pain is a distinctive pathology that can be present in children and adolescents and is often overlooked by practitioners. Its diagnosis and management are challenging in this population as it is in adults. SI joint steroids injections may play a role in the management of these patients.